Penyembunyian Pesan Teks Tersandi dengan Algoritma Massey Omura Pada Gambar Berdasarkan Metode Stegano F5 - Herianata Barasa (Journal of Informatics Management and Information Technology, 2021)
In the current era of computerization, securing data is a very important thing to do, especially on confidential data. Because if there was data breach, for example in messages containing secret text, it would be detrimental to those concerned. Therefore we need a system that can secure these text messages. The tighter the data security is, the less likely it is to be compromised. In this study the authors will combine two methods in securing text messages. Namely the Massey Omura method and the Stegano F5 method. The author will use the Massey Omura method to encode messages which are then hidden in the image using the Stegano F5 method. The Massey Omura algorithm is an algorithm that works with the concept of asymmetric keys and is developed based on the concept of a three-pass protocol. The three-pass protocol works with the concept that each party (recipient and sender of the message) uses their own key to encrypt and decrypt messages. One of the advantages of the Massey Omura algorithm is the difficulty of calculating discrete logarithmic which is similar to other public key algorithms such as RSA, and others. And Stegano F5 is a very early version for embedding files into native color BMP, GIF, or JPEG images. The combination of the Massey Omura algorithm with the Stegano F5 method, will make it very unlikely that other parties can break into confidential messages.